A Comparative Study of Post-Operative Pain at Port-Site After Gallbladder Retrieval From Umbilical Ports Versus Epigastric Ports in Laparoscopic Cholecystectomy (Medical Forum Monthly, 2024)
Objective: To evaluate the difference in the results of laparoscopic cholecystectomy performed via umbilical and epigastric ports after gallbladder removal.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the department of Surgery, Central Park Teaching Hospital, Lahore from January 2023 to June 2023.Methods: Data collection: 100 patients; 50 in each group fulfilling selection criteria were enrolled for the study and were randomly divided in two groups. Time taken for retrieval of gallbladder, post-operative pain, bleeding, complete wound healing, re-operation were noted during follow-up. SPSS v. 25 was used to analyse the data.Results: Mean age of the patients in umbilical port group was 44.96 ± 16.63 years and in gastric port group was 43.40 ± 15.21 years. In umbilical port group, the mean time for retrieval of gall bladder was observed as 3.96 ± 0.83 minutes and in gastric port group was 5.80 ± 1.20 minutes (p < 0.001). In umbilical port group, the mean pain score after 24 hours was 3.20 ± 0.89 and in gastric port group was 4.74 ± 1.16 (p < 0.001).Conclusion: Umbilical port gall bladder retrieval is preferable to gastric port because it requires less time in surgery, causes less discomfort, and has a higher rate of success.